A three-scale framework for fibre-reinforced-polymer curing Part I: Microscopic modeling and mesoscopic effective properties. (1st December 2016) - Mahnken, Rolf; Dammann, Christian
Abstract: Our work presents a three-scale model for temperature-dependent visco-elastic effects accompanied by curing, which are important phenomena in a resin transfer molding (RTM) process. In Part I, bounds for the bulk quantities of the matrix material in dependence of the degree of cure for an equally distributed, homogeneous mixture with phases resin, curing agent and solid are derived. Furthermore, effective bulk quantities are obtained by homogenization for a representative unit cell (micro-RVE) on the heterogeneous microscale, taking into account the geometrical arrangement of phases. To this end, an analytic solution is derived by extension of the composite spheres model known from the literature. For simplification, we restrict the material behavior of the micro-RVE to linear thermo-chemo-elasticity. In a study we compare different meso material properties including bounds and effective material constants. In the examples we compare the meso-micro relations for the homogeneous matrix with those derived for the heterogeneous matrix.